Urban green areas with mixed vegetation favor avian richness and abundance in Ciudad Victoria, Tamaulipas, Mexico - Gómez-Moreno, Vannia del C. (2023)
Introduction: The presence and structure of vegetation in urban areas have an impact on the composition of bird communities. Green areas with a higher ratio of introduced vegetation tend to have a greater homogenization of avifauna, whereas green areas with a high ratio of native vegetation have a greater diversity of birds. In several studies carried out in urban areas of Mexico, the factors of vegetation are not considered. Therefore, the responses of the species to vegetation types in terms of richness and diversity are unknown. Objective: To analyze the composition of bird species in the green areas of Ciudad Victoria, Tamaulipas, and evaluate the response of bird communities in areas with differences in vegetation composition. As well as to analyze the relationship between the trophic guilds in birds and vegetation in urban areas. Methods: Three sampling sites were established in Ciudad Victoria, Tamaulipas, Mexico, based on two criteria: similar sampling area (ha) and differences in vegetation characteristics. Monitoring took place between January and December 2020, with three monthly visits in each site for a total of 108 visits, using the direct visual method. Results: We identified 98 species (11 orders, 28 families). The most abundant species were Quiscalus mexicanus and Molothrus aeneus. Differences in species richness were found for each site. The insectivorous and granivorous were the dominant guilds. An association between the guilds and the study sites was determined, where most were linked to mixed native vegetation, compared to homogeneous or introduced vegetation. Conclusions: The urban areas studied maintained a notable number of birds, and several of them presented some category of risk or endemism. This demonstrates the importance of these green areas composed of native vegetation as a refuge for birds and highlights the need to conserve and protect these areas within Ciudad Victoria and similar cities.